Metals release from stainless steel knives in simulated food contact. Issue 3 (3rd July 2022) - Casaroli, Andrea; Boniardi, Marco; Gerosa, Riccardo; Bilo, Fabjola; Borgese, Laura; Cirelli, Paola; Depero, Laura E.
ABSTRACT: The release of chromium, nickel, and manganese from knives stainless steel produced in Italy and People's Republic of China was investigated with the aim to check their quality and compliance with Italian Ministerial Decree 21.03.73, which is the most detailed text for the hygiene regulation of packaging, containers, and tools intended for food contact. Temperature effect on metal release is investigated in 18 sets of knives. Tests are performed by simulating discontinuous contact using a 3% glacial acetic acid solution in distilled water at 50°C and 100°C. Chromium, nickel, and manganese quantification is performed by total reflection X-Ray fluorescence. Chemical composition highlights low sulphur content, and most of them belong to the American Iron and Steel Institute (AISI) 420 type A stainless steel group. Tests performed at 100°C revealed higher concentration of released metals. Only three knives tested at 100°C exceed the limit of 100 µg L −1 .